Implementation of Augmented Reality as Information and Promotion Media on Dieng Tourism Area - Banu Nur Affan; Agus Suryanto; Arief Arfriandi (Universitas Ahmad Dahlan, 2018)
Information and promotion became necessary for tourists to get also improve their knowledge of tourism and their experiences about the tourist destination. Dieng tourist area had manytourist attractions and would be styled to be promoted at the world level tourism by Central Java government in Indonesia, but tourist information and promotional media not yet structured and interactive, as well as the need of media that can provide knowledge, experience for tourists with packaged in an interactive and interesting way. The purpose of this research is to produce Augmented Reality application that could visualize information of Dieng tourism objects, as an interactive, interesting information and tourism promotional media. The user would get information about every tourist attraction in Dieng through the augmented reality application that contains many contents about the sites by scanned Natural Marker that already exist in every Dieng tourist attraction sites with his smartphone.